PARTICIPATION OF THE CYTOPLASMIC MEMBRANE IN THE GROWTH AND SPORE FORMATION OF BACILLI - Fitz-James, Philip C. (The Rockefeller University Press, 1960)
A polyester embedding technique was used to study the early stages of spore formation in members of the genus Bacillus in order to investigate further the origin and nature of the initial spore septum and the resulting forespore envelope. Whereas previously, with a methacrylate procedure, this layer had appeared to be continuous with the cell wall, this study reveals it as a double layer of cytoplasmic membrane. Perisporal, membranous organelles connected both to the developing forspore envelope and to the cytoplasmic membrane were encountered in the four species studied. Similar organelles were prominent during growth at the sites of transverse septa formation. These were connected to, or continuous with, the cytoplasmic membrane and often adherent to the chromatin bodies of the dividing bacilli.